Analysis of Quality Control of Drawn Textured Yarn Using Six Sigma Method at Indorama Engineering Polytechnic Production Unit - Ulum, Rikzan Bachrul; Agassi, Andre; Muchtar, Diki (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2025)
Drawn textured yarn is one of the production outputs of the Vocational Training Center at Politeknik Enjinering Indorama, a partner of PT Indorama Synthetics Tbk. In its production process at the Vocational Training Center of Politeknik Enjinering Indorama, product defects are still encountered. To reduce product defects, the Six Sigma method with DMAIC approach is employed. For companies prioritizing product quality, quality control over the products must be conducted. This can manage and control the number of rejected or damaged products that could potentially harm the company's reputation in the eyes of consumers when the products are marketed.